Pengaruh Penggunaan Serat Kulit Jagung dan Abu Sekam Padi Sebagai Bahan Campuran Pembuatan Asbes Plafon - Arizal Fadli Fitrianto; Hartono H; Asri Nurdiana (Universitas Diponegoro, 2024)
Agricultural waste is one of the most common sources of waste in Indonesia, corn husk fiber and rice husk ash are examples of this agricultural waste. In this study, corn husk fiber and rice husk ash were used as a mixture for making asbestos ceilings. This study used an experimental method by using corn husk fiber as a substitute for fiberglass fiber and rice husk ash as a partial substitute for cement. Corn husk fiber has high flexural properties which are assumed to be able to replace fiberglass fibers in the manufacture of asbestos ceilings. Meanwhile, rice husk ash contains silica (SIO2), which is one of the compositions of cement. Therefore, it is proposed to innovate the use of corn husk fiber and rice husk ash as a mixed ingredient for making asbestos ceilings which aim to minimize existing waste and create environmentally friendly asbestos ceilings that have better flexural strength and water absorption than conventional asbestos ceilings. This innovation is expected to produce a more economical price.